Factors that Influence and Maintain the Market-Leading Position of PT. Pegadaian (Persero) - Andayani Sihaloho (Priviet Social Sciences Journal, 2024)
This study aims to examine the extent to which Quality of Care, Emotional Closeness, and Product Diversification create Customer Loyalty and maintain the position of market leader. PT. Pegadaian (Persero) is a financial services company. In this study, path analysis was used to process the data. Applications 20.0 for Windows was used to process the data. The results of this study indicate that there is a positive and significant correlation between service quality, emotional closeness, product diversification, no customer loyalty, and market leadership. The direct influence of service quality on customer loyalty was 24%. The amount of emotional closeness directly influences customer loyalty. The amount of direct influence was 59.9%. The number of emotional closeness variables that directly influence the market leader is equal to 37.5%. The amount of direct influence on the product diversification variable market leader is equal to 39.8%. The indirect effect of the variable "quality of service" on the market leader through customer loyalty is equal to 5.54%. The indirect effect of the product diversification variable, market leader/market leader, on customer loyalty is 4.62%.